Escape behavior of rocky‐reef fish reveals the impact of spearfishing across different management regimes - Francisco J. Contreras‐Drey; Natalio Godoy; Andrés Smith; Enrico L. Rezende; Alejandro Pérez‐Matus; Rodrigo A. Estevez; Ricardo Beldade; F. Patricio Ojeda; Stefan Gelcich (Ecosphere)
Abstract Flight initiation distance (FID), the distance at which an organism begins to flee from an approaching threat, is a major component of antipredator escape behavior and a potential indicator of threat perception in fishes. In this study, we analyzed the FID of three important rocky‐reef fish species targeted by spearfishers, which are of commercial and recreational importance. We tested predictions that FID to a diver threat increases with the following factors: (1) fish body size, (2) less restricted access regimes, and (3) increased historical fishing pressure. We studied three size ranges of three rocky‐reef fish species, in three different access regimes (i.e., open access, territorial user rights for fishery areas, no‐take marine protected areas), and in two regions (northern and central region with different levels of fishing pressure depending on the species). We conducted an ANOVA to analyze pairwise interactions. We used the mean square criterion to select the models that best explained the variation of our response variable. Our findings indicate that FID can be distinctly elucidated by factors such as individual size, species, access regimes, and regions. Additionally, our models show that interactions involving regions and either species or size further contribute to explain FID variability. FID was higher in larger fishes and those of higher commercial value, outside marine reserves and in the region with the highest historical fishing pressures (based on landings data). This study supports the predictions that increased FID is associated with the threat posed by spearfishing activities. Furthermore, our findings indicate that spearfishing may already be altering the behavior of rocky‐reef fishes on the north‐central coast of Chile.